Pretreatment of seawater: Results of pilot trials in Singapore - Chua, K T; Hawlader, Mohammad Nurul Alam; Malek, A (ELSEVIER, 2003)
In this paper, performance of different pretreatment systems used in the seawater reverse osmosis desalination process is presented. The different pretreatment techniques analyzed included conventional media-filtration technique and non-conventional membrane filtration techniques. For the membrane filtration techniques, two ultrafiltration and one microfiltration pilot plants were used in the experimental study. During the experiments, the silt density index (SDI) of the filtrate samples was regularly measured to quantify the performance of pretreatment systems in rejecting colloidal particles. Measurements of other important parameters included filtrate flux, transmembrane pressure, total suspended solids, colloidal silica, total organic carbon, etc. According to the experimental findings, the quality of the filtrate produced by the conventional media-filtration technique was inferior and highly inconsistent. SDI of filtrate varied from 2.8 to 3.8 and spikes as high as 6.3 were frequently observed. Membrane pretreatment produced filtrate of a better quality. SDI of the filtrate produced was consistently below 3.0, a prerequisite for proper operation of a RO desalination plant. The ease of operation of the membrane pretreatment processes was also noted. Together with improved maintenance procedures such as filtrate backwashing and air scouring, complete flux and pressure recoveries were achievable with minimal use of chemicals during the experiments.